RESPON TANAMAN CAISIM TERHADAP PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT DIPERKAYA ABU BOILER - Eliartati Eliartati; Iskandar Iskandar; Basuki Sumawinata (UIR Press, 2015)
This research was aimed to study the response of mustard to oil palm empty fruit bunch (EFB) compost enriched boiler ash application. Each of EFB compost produced by opened method (K1) and by closed method (K2) were treated with four levels of boiler ash doses (A0 = 0%, A1 = 5%, A2 = 10%, and A3 = 15%). Both of materials are mixed and incubated for 2 weeks. Then boiler ash-enriched EFB compost were mixed with soil (compost: 20% and soil: 80% by volume) and used as medium to grow mustard in green house experiment. The experiment was designed in completely randomized design with 9 treatments and 3 replications. The treatments were comprise of control, K1A0, K1A1, K1A2, K1A3, K2A0, K2A1, K2A2 and K2A3. The results showed that EFB compost enriched boiler ash increased growth, yield and N, P, K, Ca, and Mg content of mustard. The yield of mustard increased about 173.5 – 226.5% for K1 and 279 – 290% for K2 compared to control (68 g/plot).